2012
DOI: 10.1212/wnl.0b013e318266fa89
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate is associated with a higher risk of seizures in patients with gliomas

Abstract: Relative increased glutamate concentration in gliomas, and altered glutamate transporter expression, are associated with the presence of TAS and may play a mechanistic role in their pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
120
1
6

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(130 citation statements)
references
References 32 publications
3
120
1
6
Order By: Relevance
“…Another experimental study supports this hypothesis: Both in glioma models based on a human cell line, and based on primary cell cultures, network hyperexcitability and EEG changes were shown to be dependent on excessive glutamate release (rather than loss of uptake), as the cystine-glutamate exchanger, the so-called system x c − , was found to be upregulated in glioma cells, and more importantly, blocking this transporter system with sulfasalazine also blocked epileptiform activity and EEG changes (Buckingham et al, 2011). Taken together, these results suggest that glutamate can be released from gliomas and may in fact act as excitotoxic and epileptogenic agent (Yuen et al, 2012). Weakening of GABAergic inhibition may actually be a complimentary factor.…”
Section: Q8mentioning
confidence: 84%
“…Another experimental study supports this hypothesis: Both in glioma models based on a human cell line, and based on primary cell cultures, network hyperexcitability and EEG changes were shown to be dependent on excessive glutamate release (rather than loss of uptake), as the cystine-glutamate exchanger, the so-called system x c − , was found to be upregulated in glioma cells, and more importantly, blocking this transporter system with sulfasalazine also blocked epileptiform activity and EEG changes (Buckingham et al, 2011). Taken together, these results suggest that glutamate can be released from gliomas and may in fact act as excitotoxic and epileptogenic agent (Yuen et al, 2012). Weakening of GABAergic inhibition may actually be a complimentary factor.…”
Section: Q8mentioning
confidence: 84%
“…Abnormalities include increased expression of specific glutamate receptor subtypes, low activity of glutamine synthetase, high glutamate concentrations in glioma cells, and almost absent intracellular uptake with excessive extracellular levels. These changes correlate with higher seizure frequency and may affect tumor progression [39,40]. Radiological investigations after a first seizure may lead to the diagnosis and treatment at an earlier stage than in patients without epileptic seizures.…”
Section: The Impact Of Epilepsy On Survivalmentioning
confidence: 99%
“…Ultimately, however, the explanation is likely related to the inexorably destructive nature of high grade tumours, and to the molecular mechanisms involved with tumour growth and progression [45], which progressively impair mechanisms associated either with spontaneous seizure termination, or with the stability of the post-seizure refractory period.…”
Section: Direct Relationship Between Tase and Who Gradementioning
confidence: 99%
“…All known glutamate receptor subtypes (a-amino-3-hydroxy-5-methyl-4-isoaxazolepropionate acid [AMPA-R], N-methyl-D-aspartate [nMDA-R], kainite and metabotropic) are expressed by glioma cells [20,21,45,46,47]. Importantly, Aronica et al demonstrated increased NR2A and NR2B (stimulatory NMDA receptor subunits) expression in 41 patients with LGG compared to controls [46].…”
Section: Glutamate Receptorsmentioning
confidence: 99%